A Class of Consistent Share Functions for Games in Coalition Structure - René van den Brink; Gerard van der Laan (Tinbergen Institute, 2001)
A cooperative game with transferable utility describes a situation inwhich players can obtain certain payoffs by cooperation. A sharefunction for such games is a function which assigns for every game adistribution of the payoffs over the players in the game.In this paper we consider cooperative games in which the playersare organized into an a priori coalition structure being a finitepartition of the set of players. We introduce a general method fordefining a class of share functions for such games in coalitionstructure using a multiplication property that states that theshare of a player in the total payoff is equal to its share in someinternal game within its coalition multiplied by the share of thiscoalition in an external game between the coalitions. We show thatthese coalitionstructure share functions satisfy certain consistency properties. Weprovide axiomatizations of this class of coalition structure sharefunctions using these consistency and multiplication properties.
Keywords: 330; TU-Game; coalition structure; share function; multiplication property; consistency; Kooperatives Spiel; Koalition; Theorie